A review on the prevailing gaps in women’s sexual and reproductive health rights in Tanzania’s National Health Policy 2017 - Emmanuel Michael Massay (Jurnal Sosiologi Dialektika, 2021)
Women’s sexual and reproductive health rights (SRHR) are linked to numerous human rights; health, education, freedom from torture, protection from all forms of discrimination, and right of privacy. SRHR refers to a set of rights that every human being is entitled to, regardless of culture, race, religion, ethnicity, or disability. Women’s sexual and reproductive health rights have been taken for granted, especially in Tanzania’s health policies. However, Tanzania has several National Policies and Laws that affect women and men differently and in certain areas, they even contradict other existing laws. The prolonged poor SRHR shows the urgency of the reformation of the policies and laws. The analysis was carried out qualitatively through a reflection focused on the policy and other legal materials concerned. The study revealed that the policy does not cater enough for women’s SRHR. This study concludes that the policies are outdated and have a lot of loopholes. This has led the sexual and reproductive health system in Tanzania astray. The study concludes that the TNHP 2017 has to be reviewed and revised in order to meet the women’s SRHR and also to align it with some of the international policies and targets concerning sexual and reproductive health.